Philosophical Therapy: Spinoza's Model - Mounitz, Abraham (British Journal of Healthcare and Medical Research, 2022)
Abstract The study concerns the issue of whether philosophy can release us from predicaments ranging from mere discomfort to mental anguish. Philosophical counselling takes place dialogue in order to form a conception of the client’s mental world. During conversation, the counsellor will reveal the dilemma that concerns the client. After the latter is brough to the surface, it is possible to commence our therapeutic counselling discourse. It has recently shown that philosophical counselling possesses the power to—among rational human beings—fill in the lacuna that is present prior to psychotherapy or psychiatric therapy. Our concern with Spinoza’s applied ethics led to the formulation of a therapeutic model that has proved its effectiveness in unconventional cases of depression, and passive lethargic fixation. Philosophical therapy guides the client toward observing himself in relation to environment within the framework of accessible rational tools available to any mind capable of thought and reflection. The model is relevant to the welfare of a person placed in an unconventional situation and has been proved as filling in the lacuna present prior to contacting psychotherapeutic or psychiatric professionals. Beyond adaptation to uncomfortable situations, Spinoza’s therapeutic method promotes a meaningful life through the use of understanding and reason as a transformative tool with respect to our physical and mental well-being.